Efficacy of Antimicrobial Photodynamic Therapy as an Adjunctive to Mechanical Debridement in the Treatment of Peri-Implant Diseases: A Randomized Controlled Clinical Trial - Karimi, Mohammad Reza; Hasani, Ali; Khosroshahian, Salva (Journal of Lasers in Medical Sciences, 2016)
Introduction: The purpose of the present study was to assess the clinical effects of anti-microbial photodynamic therapy (PDT) after closed surface scaling in the treatment of peri-implant diseases. Methods: Ten patients with a total of 15 pairs of dental implants, showing clinical and radiographic signs of peri-implant diseases, were included in this study. In each patient, one implant randomly served as control implant and the other served as test implant. The control implants were treated with closed surface scaling only and the test implants received additionally PDT, using light with a wavelength of 630 nm and intensity of 2000 mw/cm2 for 120 seconds after application of photosensitizer in peri-implant sulcus. Clinical parameters were evaluated before and 1.5 and 3 months after treatment. Results: Statistical analysis showed significant differences in probing pocket depth (PPD), clinical attachment loss (CAL), bleeding on probing (BOP), and gingival index (GI) at each time point between the two groups. There were no statistically significant changes with respect to any of the parameters in the control group. Complete resolution of BOP at 3 months was achieved in 100% of test implants. At 1.5 and 3 months, there were significant differences in the mean probing depth and CAL gain measurements at implants in the test group. Conclusion: The present study revealed that adjunctive use of PDT following closed surface scaling could lead to clinical improvement of peri-implant diseases. Further studies are necessary to confirm our results